Penal Mediation Against Khalwat Settlement According to Customary Law in Aceh - Zaituni, Zaituni (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
The case of khalwat or pairing between a man and a woman who are not mahram is one of the violations regulated in Qanun Aceh Number 6 of 2014 concerning the Law of Jinayat. However, in practice, the settlement of khalwat cases in Aceh is often resolved through customary channels, utilizing the penal mediation approach, in line with Aceh Qanun Number 9 of 2008, which concerns the Development of Customs and Traditions. This study aims to analyze how penal mediation is applied in the settlement of khalwat cases, as per customary law in Aceh, and the extent to which it contributes to creating restorative justice. The method used is a literature research with a juridical-normative and sociological approach to the literature and related laws and regulations. The results of the study show that penal mediation in the settlement of khalwat prioritizes social recovery, peaceful settlement, and family values rather than formal sanctions. However, this practice faces obstacles such as the absence of standard procedures and weak coordination between customary institutions and law enforcement officials. Therefore, stronger regulations and supervision are needed to ensure that penal mediation runs fairly, legally, and follows applicable legal principles.